Adhesive Platelet Count and Blood Coagulability in Myocardial Infarction and Cerebral Thrombosis - Yamazaki, H; Odakura, T; Takeuchi, K; Sano, T (Thrombosis and Haemostasis, 1970)
In 382 patients, aged 21 to 76 years, including 39 healthy volunteers, a platelet count by Olef’s method, an adhesive platelet count by Moolten-Vroman’s method, prothrombin activity due to one-stage prothrombin time and calcium clotting time were measured. In 39 cases of myocardial infarction and 40 cases of cerebral thrombosis, both in acute stage, a marked decrease in the adhesive platelet count and adhesive index and an increase of prothrombin activity were observed with statistical significance compared to the healthy group (P < 0.01). In the recovery stage of myocardial infarction, cerebral thrombosis and other diseases, except for malignant tumors, acute infectious diseases, diabetes mellitus and blood or liver diseases, the above observations were absent or reduced. In the case of thrombosis, a negative correlation was seen between the adhesive platelet count and prothrombin activity (r — —0.238, P < 0.01). There is no correlation between the changes in platelet adhesiveness or blood coagulability and total cholesterol level in serum.